2021
DOI: 10.2147/cmar.s282989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes as Potential Prognostic Biomarkers in Cervical Cancer Using Comprehensive Bioinformatics Analysis and Validation Studies

Abstract: Background: Cervical cancer belongs to one of the most common female cancers; yet, the exact underlying mechanisms are still elusive. Recently, microarray and sequencing technologies have been widely used for screening biomarkers and molecular mechanism discovery in cancer studies. In this study, we aimed to analyse the microarray datasets using comprehensive bioinformatics tools and identified novel biomarkers associated with the prognosis of patients with cervical cancer. Methods: The differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…On the other hand, we reviewed 52 published articles associated with CC infections that provided transcriptome-guided hub proteins (genomic biomarkers) for cross-validation of the proposed key genes and the candidate drug agents. There were 255 hub genes reported in those 52 articles, with 7 hub proteins (AURKA, PCNA, CCNB1, CDC45, MCM2, TOP2A, CDK1) appearing in at least 5 articles ( Table S2 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Five (AURKA, CCNB1, MCM2, TOP2A, and CDK1) of the seven reported hub proteins were found to be similar to our suggested seven KGs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, we reviewed 52 published articles associated with CC infections that provided transcriptome-guided hub proteins (genomic biomarkers) for cross-validation of the proposed key genes and the candidate drug agents. There were 255 hub genes reported in those 52 articles, with 7 hub proteins (AURKA, PCNA, CCNB1, CDC45, MCM2, TOP2A, CDK1) appearing in at least 5 articles ( Table S2 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Five (AURKA, CCNB1, MCM2, TOP2A, and CDK1) of the seven reported hub proteins were found to be similar to our suggested seven KGs.…”
Section: Resultsmentioning
confidence: 99%
“…CDK1 contributed to the occurrence and development of CSCC [ 18 , 23 , 25 , 26 , 27 , 40 , 41 , 44 , 46 ]. MCM2 involved in the carcinogenesis of cervical cancer [ 16 , 19 , 20 , 21 , 23 , 27 , 42 ]. TOP2A is regarded as a biomarker for the improved diagnosis of CC [ 16 , 17 , 19 , 23 , 24 , 26 , 27 , 41 , 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volatile anesthetic, isoflurane, activates the histone deacetylase 6 pathway, accompanied by the upregulation of PCNA protein expression, thereby promoting cervical carcinogenesis [ 47 ]. PCNA was significantly correlated with shorter overall survival in patients with CC [ 48 ]. Lv et al [ 49 ] used CC as an example to conduct a systematic review and meta-analysis of the clinical effects of PCNA.…”
Section: Research On Pcna In Gynecologymentioning
confidence: 99%
“…Dan et al identified PLOD2, ANLN, AURKA, and AR as possible therapeutic targets of cervical cancer through comprehensive analysis of cervical cancer-related gene expression profiles combined with bioinformatics [ 12 ]. Dan et al found that CDC45, GINS2, MCM2, and PCNA may be related to the occurrence and development of cervical cancer, and further verified that MCM2 knockdown can inhibit the proliferation of cervical cancer cells [ 13 ]. Although many studies have focused on certain genes in cervical cancer, it is still far from enough to reveal the underlying pathogenesis [ 14 16 ].Therefore, the present study used bioinformatics methods to find novel prognostic biomarkers of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%